RECONCEPTUALIZING EDUCATIONAL MANAGEMENT THROUGH A CRITICAL PARADIGM: A KNOWLEDGE-BASED LITERATURE STUDY - Saprudin Saprudin; Nuryati Nuryati; Evi Gustini; Tuti Alawiah; Murnasih Murnasih (Universitas Islam Negeri Mataram, 2026)
The growing complexity of contemporary education systems has intensified the demand for effective educational management; however, prevailing practices remain largely dominated by technocratic and administrative rationalities that prioritize efficiency, accountability, and measurable performance. Such approaches tend to instrumentalize knowledge and marginalize the epistemological, ethical, and social dimensions of education. This study aims to reconceptualize educational management through a critical paradigm by examining how knowledge-based management is conceptualized, legitimized, and practiced within contemporary scholarly discourse. Employing a qualitative Systematic Literature Review with a critical–conceptual orientation, this study synthesizes peer-reviewed literature published between 2016 and 2025, with particular emphasis on recent studies. Data were analyzed through thematic content analysis and critical synthesis to identify dominant managerial assumptions, epistemological orientations, power relations, and their implications for educational management theory and practice. The findings reveal that while knowledge-based management has gained prominence, it is predominantly framed within instrumental and performance-oriented logics that reinforce hierarchical governance and limit participatory practices. By contrast, the critical paradigm repositions educational management as a knowledge-based social practice that is inherently value-laden, politically situated, and oriented toward reflexivity, dialogue, and social justice. This study contributes theoretically by integrating knowledge-based educational management with critical epistemology and offers a reflective framework for reorienting educational management from administrative effectiveness toward transformative and emancipatory practice.